Social Protection for Child Labors - Yuningsih, Yuyun; Salamah, Ummu; Nurwati, Nunung (International Journal of Engineering and Technology, 2018)
Socio-economic condition of the family often drives children to be directly involved in earning living expenses as workers. In the informal sector, Child labor is very prone to exploitation, discrimination, and violence. The purpose of this study is to discuss the implementation of social protection for child labor in Cibaduyut Region, Bandung, Indonesia. This study used descriptive qualitative approach. Informants were selected based on purposive sampling method. The informants covered child labor, family, and representation from a government agency and non-government agency involved in social protection program for child labor. Data collecting was obtained through interview and observation. The data were analyzed with the descriptive qualitative method. The research finding showed that social protection for child labor needs social assistance, social advocacy, and legal assistance. The result denoted that social protection program cannot be done effectively, comprehensively, and sustainability. This study used ecological perspective to understand the influential factors toward a social policy for child labor. Furthermore, the study recommended the enhancement of cooperation and coordination between stakeholders so that child labor can be treated effectively. Â Â